2018
DOI: 10.5812/ircmj.62969
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Semen Parameters in a Man With Idiopathic Severe Oligoasthenoteratozoospermia Using Date Palm Pollen (Phoenix dactylifera L.) Based on Iranian Traditional Medicine: A Case Report and Literature Preview

Abstract: Introduction: Almost 50% of infertilities are associated with males and among them 30to 50% are idiopathic. Empirical treatments are used in idiopathic male infertility, yet not enough scientific evidence is available for the application of such remedies. date palm pollen (DPP) is one of the drugs suggested for such patients in Iranian traditional medicine (ITM). Case Presentation: This study was performed on a 35-year-old male patient with idiopathic infertility. He previously had severe oligoasthenoteratozoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Furthermore, the protective role of DPP has been reported on the genital tract and spermatogenesis against cadmium toxicity in male rats [37]. In line with previous studies, our findings strongly confirm a significant amplification of sperm quality parameters including sperm count, motility and morphology after DPP administration in patients who suffer from IMI [38][39][40]. It is worth to note that nutritional deficiencies such as zinc and selenium are one of the risk factors contributing to male idiopathic infertility especially in terms of sperm count and motility [41].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the protective role of DPP has been reported on the genital tract and spermatogenesis against cadmium toxicity in male rats [37]. In line with previous studies, our findings strongly confirm a significant amplification of sperm quality parameters including sperm count, motility and morphology after DPP administration in patients who suffer from IMI [38][39][40]. It is worth to note that nutritional deficiencies such as zinc and selenium are one of the risk factors contributing to male idiopathic infertility especially in terms of sperm count and motility [41].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Al-Sanafi et al [ 114 ] reported that the coadministration of the same dose of DPP (500 mg) and 100 mg of zinc sulfate capsules twice daily for 3 months increased serum LH, FSH, and testosterone levels, while improving sperm count and active sperm motility. In an Iranian case report study involving a man with idiopathic severe oligoasthenoteratozoospermia, normal morphology, total motility, progressive motility, and sperm concentration impressively increased [ 124 ]. The results from these studies illustrate the ameliorative effects of DPP not only on semen quality parameters but also on the reproductive system as a whole.…”
Section: Effect Of Date Palm Pollen On Human Reproductionmentioning
confidence: 99%
“…As a result, vitamin E is largely responsible for preventing damage to the components of the sperm cell membrane, and it also plays a supporting role in the reduction of ROS generation. In experiments conducted in vitro, it was found that vitamin E increased both the motility of sperm and the penetration of hamster eggs, two factors that are essential for fertilisation [200]. In in vivo studies of male infertility, supplementation with vitamin E was shown to be beneficial in cases of oxidative stressinduced low sperm count and motility (oligoasthenozoospermia) [201].…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%